Market interactions between agricultural commodities and the dry bulk shipping market - Michail, Nektarios A.; Melas, Kostis D. (My University, 2021)
We investigate and quantify the relationship between agricultural commodities and ocean-going freight rates, using a weekly dataset from 2010 to 2019 and a Vector Error Correction Methodology. The results are firstly supportive of the view that vessel classes are highly interconnected, and secondly confirm that commodity prices can have a strong impact on freight rates across most vessel classes. For commodities in which no impact is registered on freight rates, the possibility of substitution effects exists. Furthermore, the results indicate that the markets in which these products trade can be a significant determinant of future freight rate movements. These findings can be particularly useful for agricultural businesses that are concerned with the transportation cost of their products and the ways that the latter can be mitigated.
Keywords: Agricultural commodities; Dry bulk; Shipping freight rates; Cointegration; Variance decomposition